Tomografia wiersza - Michałowski, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The present interpretation is an attempt to apply the close reading method to Bohdan Zadura’s poem „Zbuntowane komórki” [Rebellious cells]. The analysis reveals mysterious relations between the motifs of „snowless winter”, memory and a mole in the face of a close person that has been removed by plastic surgery. A juxtaposition of a landscape with a fragment of a portrait evokes particular contexts: that of beauty and aesthetics, healthiness and the unnerving medical examination that may suggest malignant tumor and, first of all, violated identity. The oncological theme intertwines with the ontological problem. In addition, the relations between the presented world in the poem and the texts turn out to be parallel: the „salubrious” classical form of the sonnet, available in the process of interpretation, is conducive to the subjugation of the cancer worry.